The American Heritage picture dictionary (Boston : Houghton Mifflin, 2003)
A picture dictionary for children ages four through six, featuring an alphabetical listing of nine hundred words, each with a color illustration, and an example sentence when appropriate.
1.5
2.5.
K-3
Keywords: English language -- Dictionaries, Juvenile; Picture dictionaries, English; English language -- Dictionaries; Picture dictionaries; English language -- Dictionaries; Picture dictionaries